1991
DOI: 10.2307/3283121
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Infracommunities of the Frogs Rana catesbeiana and Rana clamitans from Turkey Marsh, Michigan

Abstract: One hundred twenty-seven bullfrogs, Rana catesbeiana, and 120 green frogs, Rana clamitans, collected in July and August 1987 from Turkey Marsh, Michigan, were examined for helminths. Of the 16 helminth species found, Falcaustra catesbeianae had the highest prevalence and mean intensity in bullfrogs. In green frogs, Megalodiscus temperatus had the highest prevalence and Haematoloechus parviplexus had the highest mean intensity. Taxonomically, 1,030 (30.5%) trematodes and 2,348 (69.5%) nematodes occurred in bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 18 publications
7
45
0
2
Order By: Relevance
“…The results obtained by Muzzall (1991) and McAlpine (1997), in relation to the analysis of the helminth communities of different holarctic frogs, are consistent with those provided hereby on the helminth infracommunities of green frogs, although the diversity and the evenness values are slightly higher in the present study. Nevertheless, the species richness, the diversity and the abundance values of the helminth infracommunities were very low in these studied green frogs compared to the values found in the helminth infracommunities of Rana clamitans from Michigan, USA (Muzzall et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results obtained by Muzzall (1991) and McAlpine (1997), in relation to the analysis of the helminth communities of different holarctic frogs, are consistent with those provided hereby on the helminth infracommunities of green frogs, although the diversity and the evenness values are slightly higher in the present study. Nevertheless, the species richness, the diversity and the abundance values of the helminth infracommunities were very low in these studied green frogs compared to the values found in the helminth infracommunities of Rana clamitans from Michigan, USA (Muzzall et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…The revision carried out by Aho (1990) on the helminth community structure of amphibians indicates that the corresponding communities can be highly variable, although they are habitually depauperate and noninteractive in structure. Various authors (Muzzall, 1991;Goldberg et al, 1995;McAlpine, 1997;Muzzall et al, 2001;Bolek & Coggins, 2003) consider that amphibian populations provide excellent systems to study ecological concepts related to helminth communities. Therefore, the study of helArticle available at http://www.parasite-journal.org or http://dx.doi.org/10.1051/parasite/2006134291…”
Section: Discussionmentioning
confidence: 99%
“…Several amphibian studies of helminth community structures showed they are depauperate and isolationist (Aho 1990;Muzzall 1991;Yoder and Coggins 1996;Coggins 2001, 2003). Working with Lysapsus limellus Cope, 1862 and L. chaquensis in Argentina, Kehr et al (2000) and Hamann et al (2006) found no fixed pattern, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that the parasite community structure depended on many different factors, including both host and parasite life histories (i.e., coevolution) (Janovy et al 1992, Brooks et al 2006, the host's characteristic habitat, and host feeding preferences (McAlpine and Burt 1998, Muzzall 1991, Muzzall et al 2001, Bolek and Coggins 2003, Zelmer et al 2004. In addition, host species, body size and sex (Tucker and Joy 1996;McAlpine 1997;Joy and Pennington 1998;Bolek and Coggins 2001;Goldberg and Bursey 2002;Goldberg et al 2002a, b) are important factors in the intricate inter-relationships between parasites and their host in addition to the colonization probabilities of parasites.…”
Section: Introductionmentioning
confidence: 99%
“…We believe this report might have been a misidentification. Rana catesbeiana has previously been reported as hosting M. temperatus (Stafford, 1905) Harwood, 1932(e.g, Slagle, 1966Brooks, 1977;Muzzall, 1991;Andrews et aI. , 1992;McAlpine and Burt, 1998) and M. intermedius (Hunter, 1930), Harwood, 1932(e.g., Brandt, 1936, which might be a synonym of M. temperatus.…”
mentioning
confidence: 99%